Urachal yolk sac tumor penetrating the bladder as a diagnostic challenge: a case report and review of the literature - Vladimír Šámal; Tomáš Jirásek; Vít Paldus; Igor Richter; Ondřej Hes (BMC, 2022)
Abstract Background Yolk sac tumor (YST) is a germ cell tumor. It is primarily located in the gonads but can also occur extragonadally (extragonadal yolk sac tumor - EGYST), most commonly in the pelvis, retroperitoneum or mediastinum. Only a few YSTs of the urachus have been described. Case report We present a rare case report of a 37-year-old male with episodes of macroscopic hematuria. The histological specimen obtained by transurethral resection showed a solid, and in some parts papillary infiltrative, high-grade tumor with numerous areas of marked nuclear atypia and clear invasion between the detrusor bundles. Glandular pattern has been observed in only minority of the tumor. Immunohistochemistry showed significant positivity for GPC3, SALL4 and cytokeratins AE1/AE3, while KRT7 and GATA3 were negative. We concluded that the biopsy findings were consistent with urothelial carcinoma with infrequent YST differentiation. In definitive surgical specimens we found a malignant epithelial, glandular and cystically arranged tumor of germinal appearance arising from urachus. The surrounding urothelium was free of invasive or in situ tumor changes. We reclassified the tumor as a urachal YST. Conclusion EGYST was suspected because glandular and hepatoid structures were found, but the presence of these structures should be verified by immunohistochemistry.